The human circulating miRNome reflects multiple organ disease risks in association with short-term exposure to traffic-related air pollution. (April 2018) - Krauskopf, Julian; Caiment, Florian; van Veldhoven, Karin; Chadeau-Hyam, Marc; Sinharay, Rudy; Chung, Kian Fan; Cullinan, Paul; Collins, Peter; Barratt, Benjamin; Kelly, Frank J.; Vermeulen, Roel; Vineis, Paolo; et al.
Abstract: Traffic-related air pollution is a complex mixture of particulate matter (PM) and gaseous pollutants, such as nitrogen dioxide (NO2). PM exposure contributes to the pathogenesis of many diseases including several types of cancer, as well as pulmonary, cardiovascular and neurodegenerative diseases. Also exposure to NO2 has been related to increased cardiovascular mortality. In search of an early diagnostic biomarker for improved air pollution-associated health risk assessment, recent human studies have shown that certain circulating miRNAs are altered upon exposure to traffic-related air pollutants. Here, we present for the first time a global analysis of the circulating miRNA genome in an experimental cross-over study of a human population exposed to traffic-related air pollution. By utilizing next-generation sequencing technology and detailed real-time exposure measurements we identified 54 circulating miRNAs to be dose- and pollutant species-dependently associated with PM10, PM2.5, black carbon, ultrafine particles and NO2 already after 2 h of exposure. Bioinformatics analysis suggests that these circulating miRNAs actually reflect the adverse consequences of traffic pollution-induced toxicity in target tissues including the lung, heart, kidney and brain. This study shows the strong potential of circulating miRNAs as novel biomarkers for environmental health risk assessment. Highlights: Analysis of circulating miRNAs in a human population exposed to traffic pollution. The study revealed 54 miRNAs that were affected already after 2 h of exposure. These miRNAs are involved in the molecular processes of exposure-related diseases. This study highlights circulating miRNA profiles as promising sensitive biomarkers.